Pengaruh Social Media Marketing dan Citra Destinasi Terhadap Keputusan Berkunjung Wisatawan di Pantai Samudera Baru Kabupaten Karawang - Mohamad Ardwian Fizkiana; Danang Kusnanto (Peneliti.net, 2022)
The purpose of this study was to find out and analyze the correlation between social media marketing and destination image in Samudera Baru Beach, Karawang Regency, to find out and analyze how much social media marketing and destination image partial influence on Samudera Baru Beach, Karawang Regency, to find out and analyze how much Simultaneous influence of social media marketing and destination image on Samudera Baru Beach, Karawang Regency. The approach used in this study is a descriptive and verification approach. The results show that 1) There is a correlation between social media marketing variables and destination image, 2) There is a partial influence of social media marketing on visiting decisions and destination image on visiting decisions, 3) There is a simultaneous influence of social media marketing and destination image on decisions. visit. This can show that social media marketing and destination image together have an influence on the decision to visit Samudera Baru Beach.